Age Limit in Bronchiolitis Diagnosis: 6 or 12 Months? - Raffaella Nenna; Antonella Frassanito; Laura Petrarca; Greta Di Mattia; Fabio Midulla (Frontiers Media S.A., 2020)
Aim: The most frequent cause of lower respiratory tract infection in infants is bronchiolitis. Up to now there is no agreement on the upper limit age of bronchiolitis. Our aim was to identify if there are clinical differences in infants hospitalized for bronchiolitis between 0-6 months and 6-12 months of age. A secondary aim was to establish whether there was differences in terms of recurrent wheezing at 12, 24, and 36 months of follow-up.Methods: We retrospectively analyzed clinical and virological records of 824 infants hospitalized for bronchiolitis during 11 consecutive epidemic seasons. From each infant at admission to the hospital nasopharyngeal washing was collected, clinical severity was assessed and clinical data were extracted from a structured questionnaire. At 12-24-36 months after discharge, parents were interviewed seeking information on recurrent wheezing.Results: A total of 773 infants (Group1) were ≤6 months of age, while 51 were >6 months (Group 2). No differences between family history for atopy and passive smoking exposure were observed between the two groups. Respiratory syncyzial virus was detected more frequently in Group 1 and human bocavirus in Group 2. The clinical severity score (p = 0.011) and the use of intravenous fluids (p = 0.0001) were higher in Group 1 with respect to Group 2 infants. At 36 months follow-up 163/106 (39.4%) Group 1 and 9/9 Group 2 infants experienced recurrent wheezing (p = 0.149).Conclusion: We demonstrated that 0-6 months old infants bronchiolitis differs from > 6 months bronchiolitis.